Completeness Of Documents On Speedboat Seaworthiness At Pier 16 Ilir Palembang City, South Sumatra Province - Tjahjono, A Agus; Santoso, Santoso (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
In Palembang City, there are several Port Service Units, one of which is the 16 Ilir Pier Service Unit. At Pier 16 Ilir there are still many speedboats that do not complete the Ship's Seaworthiness Documents such as Ship Measurement Letters, Registration Letters (Gross Deeds), Ship Nationality Certificates (River and Lake Passes), River and Lake Ship Safety Certificates (SKKSD), and Crew Skills Certificate. This research is a type of qualitative research method, qualitative research emphasizes quality not quantity and the data collected does not come from questionnaires but comes from interviews, direct observations and related official documents. The data used are primary and secondary data to be analyzed. Based on the results of an interview survey conducted at Pier 16 Ilir Palembang City, 100% Speedboats that have not completed the ship's seaworthiness documents. The reason for the operator or ship owner has not completed the ship's seaworthiness document, namely 42% do not meet the requirements for making shipworthiness documents, 37% lack of checking ship documents, 21% do not know the procedure for making ship seaworthiness documents. Therefore, to overcome these problems, it is necessary to conduct socialization regarding the completeness of the ship's seaworthiness documents as well as the requirements in making the ship's seaworthiness documents to the ship's owner or operator and it is necessary to coordinate with the relevant agencies in the fulfillment and affirmation of the applicable rules regarding the completeness of the ship's seaworthiness documents with conduct socialization and ease of registration regarding the importance of completeness of ship's seaworthiness documents.